MANAGEMENT OF FOETAL MACERATION IN A DOE CARRYING TWIN - DEORI, S; BHUYAN, D; KALITA, D; SHARMA, D K (The Indian Journal of Animal Reproduction, 2023)
A case of foetal maceration in a non-descript doe and its successful obstetrical management is reported inthe present communication.
Keywords: Doe; Foetal maceration; Twin